CORPORATE GOVERNANCE SEBAGAI PEMICU PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PERUSAHAAN DI INDONESIA - Dista Amalia Arifah; Hendri Setyawan (Jurnal Akuntansi Indonesia, 2019)
Intangible assets proxied by Intellectual Capital play an important role as the key to success and the trigger for the creation of company’s value. The current trend is that companies have not yet focused on Intellectual Capital disclosure. With the implementation of Corporate Governance mechanism, it is expected to support the disclosure of IC, so as to add values to the company.This study aims to analyze corporate governance mechanism as a trigger of Intellectual Capital disclosure to companies in Indonesia. The population of this study was companies included in the ranking of CG implementation conducted by The Indonesian Institute for Corporate Governance (IICG) in 2011, 2012 and 2013. The sample was taken by purposive sampling method.This study used secondary data, i.e. company’s annual report where then the data were processed with simple linear regression. The result showed that corporate governance did not have any influence to intellectual capital disclosure.